Protection Effectiveness Of Bit (Beta vulgaris) Fruit Extract In Maintaining Spermatogenesis Ability In White Rats (Rattus novergicus) Induced Carbon Tetracloride (CCl4) - Anugrah, Alvyan Lantang; Eliyani, Hana; Utomo, Budi; Susilowati, Suherni; Mafruchati, Maslichah; Kurnijasanti, Rochmah (Journal of Basic Medical Veterinary, 2021)
The aim of this research was to know whether beetroot (Beta Vulgaris) extract could protect spermatogenesis by maintaining spermatogenic and sertoli cell count  in rats (Rattus novergicus) induced with CCl4. Rats were given beetroot extract daily, for 14 days and 3ml/kg BW CCl4 intraperitoneally one hour after last treatment. This study used twenty rats which were devided equally into 5 groups. K(-), the negative control group was not induced with CCL4 and only given 1% CMC-Na suspension. K(+), the positive control group was induced with CCl4 and given 1% CMC-Na suspension. P1, P2 and P3 were given beet root extract with doses of 200, 400, and 800 mg/kg BW daily before feeding. All of the beetroot treatment were given orally (2 ml). After 24 hours CCl4 induction, rats were sacrificed and testis were collected to make histology slides. The observations showed significantly different (p<0,05) in all of variables. Result showed significant differences in spermatogenic and sertoli cells between K(-) and K(+) groups, K(+) with P2 and P3 group, and showed insignificant difference between P2 and P3 group in spermatogenic and sertoli cells. The result of this research showed that beetroot extract could protect the spermatogenic and sertoli cells in male rats induced with CCl4.